The Structure of Morals and Their Deviations from Ibnul Qayyim's Perspective: Between the Mother of Morals, Satan's Temptations, and Moral Balance - Noto Sabkaguna; Nashrudin al Ghofar (Penerbit Hellow Pustaka, 2026)
This study aims to determine the origins of noble morals and the origins of despicable morals. Who plays a role in the deviation of noble morals, and how the deviation of noble morals occurs. The type of research used by the researcher is qualitative with a literature study approach and a content analysis approach. The results of the study show that the origins of noble morals are high ideals of 'uluwwul himmah' and humility and khusyu/tawadhu'. Meanwhile, the origins of despicable morals are arrogance and low self-esteem. The devil plays a major role in the deviation of noble morals. Satan distorts a person's morals by encouraging someone to underestimate tafriith or become excessive ifraath.